Social Media, Political Mobilization, and High-Stakes Testing - McKeon, Robin Tamarelli; Gitomer, Drew H. (Frontiers in Education, 2019)
Social media posts in a Facebook group organized around the issue of refusing high-stakes testing in New Jersey were analyzed to understand how individuals and organizations use social media to engage in political protest against educational policies. Posts were categorized by their theme (reasons for opposing high-stakes testing), whether they discussed political protest tactics (both traditional and virtual), and whether they contained web links to other social media sites. Interviews with Test Refusal Movement participants were conducted to supplement the Facebook analysis by providing a more nuanced understanding of how movement participants navigate online affinity spaces and how new forms of protest have transformed but not replaced traditional political protest against policies.